Early Crediting of Emissions Reduction – A Panacea or Pandora's Box? - Axel Michaelowa; Marcus Stronzik (Hamburg Institute of International Economics (HWWA), 1999)
The Kyoto Protocol sets legally binding emission targets for industrialized countries without accounting for reductions carried out prior to 2008, the beginning of the first commitment period. There exists only one exception, the project-based Clean Development Mechanism. Two other possible ways to allow crediting for early reductions are discussed in this paper, a domestic scheme and early Joint Implementation. The implications of these concepts are analyzed on a macro as well as on a micro level taking the domestic and international commitments into account. They can lead to a strong redistribution and are prone to free riding. We conclude that early crediting makes sense if it is built on clear baselines, sets incentives for innovation and provides for institutional learning. The current bill discussed in the U.S. does not meet these criteria.
Keywords: 330; Klimaschutz; Umweltpolitik; Luftreinhaltung; Selbstverpflichtung; Trittbrettfahrerverhalten; Theorie